Improving Students’ Reading Comprehension through the Pre-Reading, During-Reading, and Post-Reading (PDP) Methods: A Qualitative Study in Timor-Leste - Ximenes, Salvador Magno; Freitas, Jonita Ana (Journal of English Language and Education, 2025)
The objective of this research was to evaluate how well the teacher-student relationship supported the implementation of the PDP methods, which improved students' reading comprehension. This research used a qualitative method to understand the phenomenon in an environment. The participants in this research were six students and one English teacher, selected using the purposive sampling method. Data were collected through interviews, and they were analysed using thematic analysis to interpret the findings. The result of the study shows that the implementation of the PDP methods is important and has a positive effect on students' reading comprehension, although some students still faced some challenges in the reading activity, including having difficulty understanding the academic words. The results indicate that this method attracts students who need active engagement in reading activities to maintain their increased motivation. Therefore, this method is beneficial and important to implement in an English class to stimulate students’ learning performance, especially to improve their ability in reading comprehension.